A Methodical Approach to the Assessment of Human Resources` Interactions - Anna Pereverzieva (Journal of Entrepreneurship, Management and Innovation)
To our knowledge, there is a need to develop a methodological approach to the assessment of united communities` human resources` level of interactions, as a large group, and of separate structural unit’s – a small group. This allows us to determine the dependence of the level of interactions on the number of people who interact within a particular structure and the nature of the activity they carry out – intellectual or manual labor. The purpose of our research is to develop a methodological approach to the assessment of the level of human resources` interactions, which allows us to identify key areas and policy measures. Expert assessments and analytical dependencies are used as research tools in the article. These tools allow us to quantitatively determine the level of human resources` interactions for an individual entity. Empirical implementation of the proposed approach, using the example of two entities varying in size and nature of labor, allowed us to make a comparative analysis and to distinguish the characteristic features that are the basis for making managerial decisions. A manager acts as an expert who assesses the presence or absence of a particular event in the subordinate unit. The indicator, which characterizes the presence or absence of certain activities and the level of participation in them, is defined on the basis of managerial assessment. The next stage is to determine the interaction rate by means of certain mathematical dependencies and results` analysis. As a result of the research, we got the assessment of the level of human resources` interactions between two entities – a united community and a structural unit. The assessment revealed a dependence on the level of interactions on the entity`s size (small and large groups) and the nature of labor. The results showed that a structural unit, focused on intellectual labor and presented by a small group, has a greater level of interactions than a united community, which has a bigger size and a predominance of manual labor.